EFFECT OF ENVIRONMENTAL PRACTICES ON ECONOMIC PERFORMANCE OF MANUFACTURING FIRMS IN NIGERIA AND GHANA (Journal of Global Accounting, 2025)
This study assessed the effect of environmental practices on economic performance of manufacturing firms in Nigeria and Ghana. The study employed Ex-Post Facto research design. The population of the study comprised all manufacturing firms in both Nigeria and Ghana listed on the Exchange Group and Stock Exchange respectively, and a sample of eleven (11) manufacturing firms in both Nigeria and Ghana was taken. Data were sourced from the various annual reports of the sampled manufacturing firms deposited in the libraries and website of the NGX (www.ngxgroup.com) and GSE (www.gse.com) spanning from 2012-2023. Data were analyzed with descriptive statistics, and the hypothesis was tested with inferential statistics panel regression analysis. The evidence provided by the regression result showed that environmental disclosure had a negative coefficient of -571106.7 and a p-value of 0.000 which was significant at 5% level for Nigeria manufacturing firms; while a positive coefficient of 3586.402 (p-value 0.133) for Ghanaian manufacturing firms, but has no significant effect. Based on the outcome of the study, the study recommended that environmental disclosure shows negative significant for Nigerian firms and positive insignificant for Ghanaian firms. Nigerian government agencies should improve on the Environmental performance evaluation system. Compared with Western developed countries Ghanaian Environmental disclosure system is not yet comprehensive, and the quality of Environmental disclosure varies.
Keywords: Environmental practices; Economic performance; Ghana; Nigeria